Pengaruh Efektivitas Sanksi Pajak Kendaraan Bermotor Terhadap Kepatuhan Wajib Pajak Orang Pribadi Dengan Tingkat Penghasilan Wajib Pajak Sebagai Variabel Moderasi Studi Kasus Kantor Sistem Administrasi Manungal Satu Atap (SAMSAT) Kota Palangka Raya Tahu - Gusti ahmad arif (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
The purpose of this study is to determine the effect of the effectiveness of motor vehicle tax sanctions on individual taxpayer compliance with the level of taxpayer income in Palangka Raya city, the sample of this study is people who pay motor vehicle tax in Samsat Palangka Raya City. Sampling in this study used a purposive sampling approach. Based on these criteria, a sample of 100 respondents was obtained. The results of the study explain that the variable moderating the Income Level of Taxpayers can affect the relationship between the Effectiveness of Tax Sanctions and Taxpayer Compliance. But the influence is a negative influence. This means that the higher the level of income of a taxpayer, the more taxpayer compliance decreases even though the taxpayer knows clearly about what tax sanctions will be received if he does not comply with paying or is late in paying motor vehicle tax.